(untitled) (Revista Innova Educación, 2022)
The research objective was to design an incomplete story strategy model to develop critical and creative thinking in 4-year-old children. The research was basic propositional with a non-experimental design and a quantitative methodological approach. We worked with a sample of 92 children from the Initial Educational Institution No. 004 of Chiclayo (Lambayeque - Peru) who were randomly selected. A test on critical and creative thinking was developed and applied in which subdimensions and indicators were considered. This instrument was validated by expert judgment. As a result, it was found that more than half of the children had an average level of development of critical and creative thinking. Therefore, it was concluded that the proposed model is a novel contribution to education by allowing children to improve these thoughts when the said proposal is applied.